Scaffold modifications to the 4-(4, 4-dimethylpiperidinyl) 2, 6-dimethylpyridinyl class of HIV-1 allosteric integrase inhibitors. (1st August 2022) - Parcella, Kyle; Patel, Manoj; Tu, Yong; Eastman, Kyle; Peese, Kevin; Gillis, Eric; Belema, Makonen; Dicker, Ira B.; McAuliffe, Brian; Ding, Bo; Falk, Paul; Simmermacher, Jean; et al.
Graphical abstract: Abstract: Allosteric integrase inhibitors (ALLINIs) of HIV-1 may hold promise as a novel mechanism for HIV therapeutics and cure. Scaffold modifications to the 4-(4, 4-dimethylpiperidinyl) 2, 6-dimethylpyridinyl class of ALLINIs provided a series of potent compounds with differentiated 5/6 fused ring systems. Notably, inhibitors containing the 1, 2, 4-triazolopyridine and imidazopyridine core exhibited single digit nM antiviral potency and low to moderate clearance after intravenous (IV) dosing in rat pharmacokinetic (PK) studies. The 1, 2, 4-triazolopyridines showed a higher oral exposure when compared to the imidazopyridines. Further modifications to the C5 substituent of the 1, 2, 4-triazolopyridines resulted in a new lead compound, which had improved rat IV/PO PK compared to the former lead compound GSK3739936, while maintaining antiviral potency. Structure-activity relationships (SAR) and rat pharmacokinetic profiles of this series are discussed.